Eksplorasi Keanekaragaman Tumbuhan Tingkat Rendah sebagai Materi Pengembangan Modul Plantae Berbasis Kontekstual - Sengka, Rani; Yani, Ahmad; Sahriah, Sahriah (INSTITUT AGAMA ISLAM NEGERI AMBON, 2022)
The diversity of low-level plants has been known for a long time and until now studies on lower-level plants are still being studied and increasingly being developed. Therefore, this study aims to identify the diversity of low-level plants in Labae village which can be used as a source of material for developing contextual-based modules in the village of Labae. plantae material in class X Senior High School (SHC). This study uses a survey method with exploratory techniques, namely research conducted by exploring areas where lower plants can be found by setting more thoroughly or thoroughly in a study. From the results of the study, it was found that there were 6 Thallophyta species from the fungal division, 3 Bryophyta species, and 8 Pteridophyta species. These low-level plant species will later be used in the development of contextual-based teaching materials in the form of modules for Plantae material in class X SHC. Keywords: Exploration, Module, Low Level Plants